Workshop and Training on Utilizing Google Forms for Junior High School Teachers - Sulistyo, Henny Wahyu; Wijaya, Guruh; Arifin, Zainul; Fitriyah , Nur Qodariyah (Journal Of Humanities Community Empowerment, 2025)
The integration of digital technology in education has become increasingly essential, especially for teachers in remote areas who often face limitations in infrastructure and digital literacy. This community engagement program aimed to enhance the competencies of junior high school teachers in using Google Forms as a tool for teaching and school administration. The training was conducted over three days, from March 10 to 12, 2025, at SMP Muhammadiyah 2 Kalisat in Jember, involving 25 teachers from various subject areas. The training methods included lectures, demonstrations, hands-on practice, and interactive discussions. Results showed that 88% of participants were able to use Google Forms independently after the training, and all participants successfully created forms tailored to their teaching needs, such as quizzes, attendance sheets, and surveys. The program received enthusiastic participation, with 100% attendance throughout the sessions. Initial technical difficulties, such as unfamiliarity with Google accounts and English-language menus, were effectively addressed through direct mentoring. The training demonstrated that practical, context-based instruction with continuous support significantly improves teachers’ digital skills. Further training and supportive school policies are needed to ensure the sustainable use of technology in education. This initiative represents a strategic step toward equitable digital transformation in schools, particularly in underserved regions